286 Barriers and opportunities for optimizing pathology mentoring in the project ECHO tumor board program of the IGC:A pilot examination of adequacy of pathology case presentations. (13th November 2020) - Plotkin, A; O'Connor, S; Rabban, J
Abstract : Introduction as part of the IGCS global education curriculum since 2017, monthly tele-mentoring of gynecological oncology fellows has been implemented at 14 cancer centers in low-middle income countries (LMIC) using the Project ECHO technique of tumor board-style videoconferences (TBVC). The effectiveness of pathologist mentors in this curriculum has not been studied and we hypothesize that it is defined, in part, by the adequacy of the pathology case presentation in pre-meeting materials and during the TBVC at each site. Methods the cancer centers of the IGCS-sponsored TBVC are in Kenya, Ethiopia, Uganda, Mozambique, Zambia, Kazakhstan, Belarus, Nepal, Vietnam, Fiji, Guatemala, Bahamas, Jamaica and PARSGO. This study is a descriptive analysis of the experiences of the initial 3 pathologists. Results attendance of the TBVC by a local site pathologist routinely occurs in 2/14 sites. Pre-meeting distribution of the pathologic diagnosis to the mentors occurs in 3/15 sites. The overall subjective assessment was that the pathologist mentors were routinely limited in their ability to evaluate the pathology of the case at 12/14 sites and therefore were limited in their opportunity to meaningfully contribute to the TBV. Conclusions: The role of pathology mentors in global educational programs for gynecological oncologists in LMIC is dependent on interaction with a local pathologist and on the adequacy of the pathology case presentation. We recommend that a standardized set of pathology information be presented for each case, including appropriate digital images, which may be a challenge due to resource limitations in LMIC without external funding.